Primary Health Care and Community Pharmacy in Ireland: a lot of visions but little progress - Martin C. Henman (Centro de Investigaciones y Publicaciones Farmaceuticas, 2020)
Ireland is small country with a population of 4.8M which spent 6.9% of its gross domestic product on healthcare in 2018. Health services are provided through a twin track approach - all public services are largely free to those eligible (32.44% in 2019) and private patients pay for most services. Most of the expenditure on medicines is paid by the government while visits to General Practitioners (GPs) are an out-of-pocket expense for private patients under 70 years of age, and private health insurance provides cover for most hospital services. Healthcare professionals in the primary care sector contract to provide public services with the Health Services Executive (HSE) which is responsible for the day-to-day running of the service. Primary care teams began to be formed in 2001 to try to link and integrate the provision of care but since these are led by GPs neither community pharmacists nor dentists joined these teams. The focus of policy remained the primary care team until a proposal to create a public health service to provide universal health coverage called Sláintecare was agreed in 2017. However, implementation of Sláintecare has been slow and piecemeal. The government regularly devises policies to control prescribing and the HSE, together with other regulators has implemented generic substitution and preferred drugs and limited access to expensive drugs through schemes for particular patient groups. A programme called Healthy Ireland has taken on the health promotion policies but pharmacists have been excluded from most programmes although some campaigns have included them. Community pharmacy organisations have tried to develop pharmacy services and while a few which are targeted at specified patient groups, such as opioid substitution, emergency administration of certain drugs, emergency hormonal contraception and seasonal influenza vaccination have been remunerated for public patients by the HSE, other services have not. GP organisations defend their members' scope of practice and seek to influence policy makers to channel schemes and services through general practice. There is no professional body to represent pharmacists that is independent of any trade union responsibilities and this has weakened the profession's advocacy. Pharmacists are one of the most trusted group of professionals in Ireland and have maintained their practices throughout periods of recession and declining income from government. Whether pharmacists can argue that the optimisation of a patient's medicines depends upon their contribution and will benefit the health service remains an open question.